Urgensi Teknologi URGENSI TEKNOLOGI DALAM PEMBELAJARAN PENDIDIKAN ISLAM UNTUK MEWUJUDKAN PROGRAM MERDEKA BELAJAR & PENDIDIKAN ISLAM YANG BERKEMAJUAN : Pemanfaatan Teknologi dalam Pembelajaran Pendidikan Islam, Urgensi Pemanfaatan Teknologi dalam Pembelajaran Pendidikan Islam - Afaf Wafiqoh Nusaibah Nusaibah; Betty Mauli Rosa Bustam Bustam (Qolamuna : Jurnal Studi Islam, 2023)
The Urgency of Using Technology in Islamic Education Learning to Realize the Free Learning Program and Progressive Islamic Education. The purpose of writing this article is to answer how to use technology in Islamic education learning and what platforms are, and to answer whether the use of technology in Islamic education learning is important or even vice versa. The type of research used in writing this article is using a type of qualitative research. The approach used is library (library research). Types of applications that can assist educators in supporting Islamic Religious Education learning are in the form of Canva, Toontastic, Lectora, KineMaster, Powtoon, Prezi, Wondershare Filmora, and Sigil applications. These applications can be used by educators in making learning media for Islamic religious education. The condition of students in the current era is different from students in previous eras so that the application of technology is an important effort in the process of teaching and learning activities. Keywords : Technology, Free Learning, Islamic Education)